Evaluation of the effects of acid mine drainage on soil characteristics and nutrient availability in agricultural land: A case study of Pesouha Village, Kolaka Regency, Southeast Sulawesi - Tambara, Ansyar; Fahruddin, Fahruddin; Patanjengi, Baharuddin (Journal of Degraded and Mining Lands Management, 2025)
The Kolaka Regency has significant mining potential; however, mining activities in this area have environmental impacts, particularly on agricultural land in Pesouha Village. This study examined the effects of acid mine drainage on the soil conditions of agricultural land and its influence on nutrient availability of Pesouha Village, Kolaka Regency. The method included direct observation at the agricultural site in Pesouha Village; the selection of sampling stations based on distance from the irrigation contaminated by acid mine drainage, comprising Station 1, Station 2, Station 3, and Station 4 as a control; assessment of soil conditions and characteristics; and soil sampling at each station for nutrient analysis, including organic carbon, total nitrogen, and the availability of phosphorus and potassium. The results indicated that the agricultural soil has a clay texture and has been contaminated by acid mine drainage, as evidenced by the reddish-brown color of the soil at the three stations, except for Station 4, which exhibited a grayish-black color. Furthermore, rice growth was abnormal, characterized by stunted plants and some leaves displaying pale yellow coloration. The levels of carbon, nitrogen, phosphorus, and potassium were all relatively low at Stations 1, 2, and 3, as well as at Station 4, except for organic carbon, which was optimal at Station 4, following the standards set by the National Standardization Agency (BSN) at the Ministry of Agriculture.